Estimation of Magnesium Level in Controlled and Uncontrolled Type 2 Diabetes Mellitus and its Correlation with Glycated Hemoglobin in Premenopausal Women - Maninder Kansal,; Kirti,; Sumit Kumar,; Suraj Kumar, (International Journal of Pharma and Bio Sciences, 2021)
Type 2 diabetes mellitus (T2DM) is a chronic disorder and has a high prevalence rate in developing countries and in populations undergoing “westernization” or “modernization”. Intracellular magnesium plays a key role in insulin-mediated-glucose-uptake. We planned this study with the purpose to find the correlation between magnesium and glycated haemoglobin levels in controlled and uncontrolled type 2 diabetes mellitus in premenopausal women. In the present observational study, 210 premenopausal women patients were divided into three groups: group I includes 70 normal healthy premenopausal women (HbA1c <5.7%) as controls, Group II includes 70 controlled diabetic patients without complications (HbA1c <7%) and group III includes 70 uncontrolled diabetic patients without complications (HbA1c ≥7%) and were matched by age. The mean glycated hemoglobin (HbA1c) was 4.0 ± 0.4 % in healthy controls, 6.3 ± 0.78 % in controlled DM group and 10.67 ± 2.0 % in uncontrolled DM group. Mean serum magnesium levels were 1.56 ± 0.18 mg/dL in controlled DM group and 1.35 ± 0.30 mg/dL in uncontrolled DM group. It showed a significant reduction in the mean of the plasma levels of magnesium in diabetic groups when compared with the control group (p < 0.05). There was an also strong negative correlation between the plasma levels of magnesium and HbA1C levels (r = -0.100, p=0.003) in diabetic premenopausal patients. Thus, our study concludes that hypomagnesemia is associated with poor glycaemic control in premenopausal women. Large-scale randomized clinical trials are required in order to determine whether the correction of Mg2+ deficiency improves the glycaemic control.